Work-in-Progress-Design and Evaluation of Mixed Reality Programs for Cybersecurity Education - Shen, Chien Chung; Chiou, Yan-Ming; Mouza, Chrystalla; Rutherford, Teomara (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
With the shortage of cybersecurity professionals, there is a critical need to train more young-generation cybersecurity professionals to fill the gap. In this work, we designed interactive activities that make abstract cybersecurity concepts more tangible by using exciting new mixed reality (MR) technology to teach cybersecurity skills and raise the potential interest in cybersecurity careers for middle school students. We plan to analyze the immersive experience, situational interest, and workload after the experiment to study the participants' learning performance and user experience.